Coordinating Care Across Settings: Roles and Responsibilities in the Primary Care Clinic (IPE Training Module for Students) - Jennifer Danielson; Megan Moore; Shanna O'Connor; Elizabeth Kaplan; Karen Manookin; Amy Kim; Karen McDonough (Association of American Medical Colleges, 2015)
Abstract This interprofessional education (IPE) program is designed to orient prelicensure students in dentistry, medicine (physicians and physician assistants), pharmacy, nursing, social work, and dietetics to roles and responsibilities in providing coordinated care for a patient with hypertension who was referred to a primary care clinic from the dentist. Students are placed in teams representing all professions present, and faculty facilitators take turns leading the program and serving as small-group facilitators. Students work together to practice team huddles where they design a care plan that capitalizes on the expertise of each team member. This 2-hour program was developed as part of a series of case-based activities conducted at the University of Washington Health Sciences Center to offer IPE opportunities to students in the 2013-2014 academic year. This program focused on engaging students in a team approach to patient care that introduced roles and responsibilities of different health professionals and encouraged contributions from each profession represented. Students were introduced to the concept of the patient-centered medical home and had the opportunity to practice team huddles and SBAR (situation-background-assessment-recommendation; a technique to promote team communication). Learning objectives for the series were drawn from the Interprofessional Education Collaborative competencies. This program was the second of six different sessions where students were put into teams for a series of activities emphasizing roles and responsibilities, team communication, shared problem solving, and team error disclosure. At the conclusion of the session, students were asked to complete an evaluation of the program via an audience response system. Overall, student perceptions of the session were positive and indicated that most students felt that the learning objectives were achieved. Mean evaluation scores (scale: 1 = Very Poor, 2 = Poor, 3 = Fair, 4 = Good, 5 = Very Good, 6 = Excellent) ranged from 4.01 to 5.42. We considered this session to be successful as one of the first interprofessional case-based activities that this particular set of health professional schools planned and delivered together on our campus.